A DISCOURSE ANALYSIS ON STUDENTS SKILL IN INTERPRETING ENGLISH SENTENCES INTO INDONESIAN IN ENGLISH INTERPRETATION CLASS DURING COVID-19 PANDEMICS - Mela Dina; Myke Fitria Sparingga (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2022)
The purpose of this research was to know about the students’ difficulties in interpreting English sentences into Indonesia in English Interpretation Class. The type of this research was qualitative research which was the case study to 8 students as the informants. They had been chosen by using purposive sampling. The data were collected by seeing the interview guided. After collecting the data, the validity of the data was tested by using prolonged engagement. Then, it was analyzed by reducing, displaying, verifying, and drawing the conclusion. Based on the result of the research, it can be concluded that there some difficulties found by the students in interpreting English sentences into Indonesian. They are: 1) Being difficult to adjust the meaning of a word with the sentence, 2) Being difficult to find a word in the dictionary, 3) Having lack of vocabulary, 4) Having lack of practice, 5) Time Pressure that contributes to nervousness, 6) Being difficult to read faster the slide show, 7) Having lack of signal, 8) Tending to translate word by word.